Artificial life IV : proceedings of the Fourth International Workshop on the Synthesis and Simulation of Living Systems - Brooks, Rodney Allen; Maes, Pattie, 1961- (Complex adaptive systems., 1994)
"The field of artificial life has recently emerged through the interaction of research in biology, physics, parallel computing, artificial intelligence, and complex adaptive systems. The goal is to understand, through synthetic experiments, the organizational principles underlying the dynamics (usually the nonlinear dynamics) of living systems. This book brings together contributions to the Fourth Artificial Life Workshop, held at the Massachusetts Institute of Technology in the summer of 1994"--Publisher's description